A designer membrane tool-box with a mixed metal organic framework and RAFT-synthesized antibacterial polymer perform in tandem towards desalination, antifouling and heavy metal exclusion. Issue 34 (16th August 2018) - Samantaray, Paresh Kumar; Baloda, Sonika; Madras, Giridhar; Bose, Suryasarathi
Abstract : A membrane tool-box designed using mixed metal–organic framework and RAFT synthesized antibacterial polymers for water remediation. Abstract : The main barrier towards quick water remediation in modern membrane based technology is multiple pre-filtration steps which target impurities like pathogens and macromolecules prior to reaching the membrane module. This pre-filtration unit requires frequent replacement, which adds to the maintenance cost. This study targets the key requirements for effective water remediation such as a stringent bactericidal response, reversible fouling, heavy metal removal and desalination packed into a single tool-box designed using a mixed metal–organic framework (MMOF) and reversible addition-fragmentation chain-transfer (RAFT)-synthesized antibacterial polymer from a quaternary ammonium compound, hyper branched amine and phosphonium based homo/co-polymers. In this module the MMOF is sandwiched between the active layer (RAFT synthesized polymer) and commercially available reverse osmosis membrane which work in tandem for effective desalination, antifouling and heavy metal removal. The selective exclusion of water through the nano-channeled MMOF and microporous active layer led to an unimpeded water flux in the range of 14–24 LMH (L m −2 h −1 ). The in vitro cytotoxicity tests on the permeate were carried out using water soluble tetrazolium (WST-1) assay and fluorescence microscopy. A 7-fold bacterial reduction mediated by generation of intracellular reactive oxygen species was observed besides unimpeded permeation of water and excellent anti-fouling properties. With >97.5% removal of divalent and monovalent salts and >95% removal of heavy metals, our membranes offer great promise in the domain of water remediation.